The Relationship Between Parental Verbal Violence And Emotional Regulation Levels In Adolescents - Erti Ikhtiarini Dewi; Lailatul Fitria; Enggal Hadi Kurniyawan; Yeni Fitria; Fitrio Deviantony (Politeknik Kesehatan Kemenkes Mamuju, 2026)
Verbal violence that occurs over a prolonged period leads adolescents to have difficulty regulating their emotions. As a result of experiencing repeated verbal violence and having low emotional regulation abilities, adolescents may replicate their experiences, become apathetic or aggressive, and exhibit delinquent behaviors. This study aims to determine the relationship between parental verbal violence and emotional regulation levels in adolescents. This research utilizes a quantitative correlational study with a cross-sectional survey design approach. The sample consisted of 172 respondents, selected through non-probability sampling, specifically purposive sampling. The research instruments were measured using the parental verbal violence questionnaire and the emotional regulation level questionnaire. Bivariate analysis was conducted using Kendall's Tau-b test. The results indicated that verbal violence against adolescents was in the moderate category as many as 107 respondents (62.2%), and emotional regulation levels in adolescents were also in the moderate category as many as 87 respondents (50.6%). The test yielded a p-value of 0.000 and a correlation coefficient of -0.557. These findings demonstrate a significant relationship between parental verbal violence and emotional regulation levels. The strength of the relationship is categorized as strong and negative in direction, meaning that as verbal violence experienced by adolescents increases, their level of emotional regulation decreases. Education regarding the impact of verbal violence needs to be provided to parents and adolescents using interesting media, and involving the role of accompanying teachers as facilitators.